HUBUNGAN ANTARA PENERAPAN STANDART OPERATIONAL PROCEDUR (SOP) PEMBERIAN OBAT PRINSIP ENAM BENAR DENGAN TINGKAT KEPUASAN PASIEN DI RST BHAKTI WIRA TAMTAMA SEMARANG: THE RELATIONSHIP BETWEEN THE IMPLEMENTATION OF STANDARD OPERATIONAL PROCEDURES (SOP) FOR THE PROVISION OF DRUG PRINCIPLES OF THE SIX CORRECT PRINCIPLES AND THE LEVEL OF PATIENT SATISFACTION AT RST BHAKTI WIRA TAMTAMA SEMARANG - Suprapti E; Azhari N.K; Lestariningsih (JURNAL KEPERAWATAN SISTHANA, 2020)
Satisfaction is a person's feelings of pleasure or disappointment that arise after comparing the results of a service that are in accordance with or not in accordance with the expectations they had before getting service. Patients as users of nursing services demand nursing services in accordance with their rights, namely quality nursing services. In providing nursing services, Standard Operational Procedure (SOP) is very important to assist nurses in achieving quality nursing care. In giving medicine, one must pay attention to the six "correct" principles which have become mandatory procedures before giving medicine, namely: right patient, right drug, right dose, right method, right time, and correct documentation. This study aims to identify the effect of applying standard operational procedures (SOP) for drug administration with the six correct principles on the level of patient satisfaction in Ungaran Hospital. The design of this research is descriptive analysis using a cross sectional approach, the number of samples used is 90 respondents using the Slovin formula to determine. The results of the study using the Chi Square analysis test showed that there was a significant effect between the application (SOP) of drug administration with the six correct principles on the level of patient satisfaction (p = 0.000). From the results of the analysis obtained the value of Odds Ratio (OR) of 59.160. The recommendation from this research is that nurses always apply the SOP correctly to increase patient satisfaction.